2012
DOI: 10.1002/jcb.24036
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic investigation of 5‐fluorouracil resistance in a human hepatocellular carcinoma cell line

Abstract: Multi-drug resistance (MDR) is a major obstacle towards a successful treatment of hepatocellular carcinoma (HCC). The mechanisms of MDR are intricate and have not been fully understood. Therefore, we employed a cell-line model consisting of the 5-fluorouracil (5-FU) resistant BEL7402/5-FU cell line and its parental BEL7402 cell line. Using relative and absolute quantification (iTRAQ)-coupled 2D LC-MS/MS, a successfully exploited high-throughput proteomic technology, in total, 660 unique proteins were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
1
31
1
Order By: Relevance
“…The highest expression of ANXA3 was detected in triple-negative breast cancer with poor prognosis as confirmed by the subsequent follow-up studies. Similar upregulation of the expression of ANXA3 is reported in prostate, ovarian, liver, rectal, and gastric cancers [10, 12, 2427]. A positive correlation between the expression of annexin and breast cancer was established.…”
Section: Discussionsupporting
confidence: 74%
“…The highest expression of ANXA3 was detected in triple-negative breast cancer with poor prognosis as confirmed by the subsequent follow-up studies. Similar upregulation of the expression of ANXA3 is reported in prostate, ovarian, liver, rectal, and gastric cancers [10, 12, 2427]. A positive correlation between the expression of annexin and breast cancer was established.…”
Section: Discussionsupporting
confidence: 74%
“…It is easy to notice that the RIs of BEL-7402/5-FU to cytotoxic drugs in our study (Table 1) are much smaller than that reported by other studies where their RIs of BEL-7402/5-FU cells ranged 160-339.7 folds for 5-FU and 13.4-26.90 folds for ADM (Jin et al, 2002;Li et al, 2004;Tong et al, 2012). The wide variation between RIs of BEL-7402/5-FU established by different research teams might be mainly due to the difference in induction methods.…”
Section: Discussioncontrasting
confidence: 66%
“…1 The mechanisms underlying the MDR of cancer cells are complex, 2, 3 including increase in drug efflux, reduction in drug absorption, changes in the targets of anticancer drugs, decrease in drug activity, enhancement of DNA repair following damage, changes in signaling pathway and so on. Classic MDR is the consequence of overexpression of transporter proteins belonging to the ATP-binding cassette (ABC) family such as P-glycoprotein (P-gp) and MDR-related protein (MRP).…”
mentioning
confidence: 99%